What determines the return to education: An extra year or a hurdle cleared? - Matt Dickson; Sarah Smith (Institute for the Study of Labor (IZA), 2011)
The 1973 Raising of the School Leaving Age in England and Wales has been used to identify returns to years' schooling. However, the reform affected the proportion with qualifications, as well as schooling length. To shed light on whether the returns reflect extra schooling or qualifications, we exploit another institutional rule - the Easter Leaving Rule - to obtain unbiased estimates of the effect of qualifications. We find sizeable returns to academic qualifications - increasing the probability of employment by 40 percentage points. This is more than 70% of the estimated return based on RoSLA, suggesting that qualifications drive most - but not all - of the returns to education.
urn:nbn:de:101:1-201104113978
Keywords: I21; I28; J24; 330; returns to education; RoSLA; qualifications; Bildungsertrag; Allgemeinbildende Schule; Dauer; Schätzung; Großbritannien